Justiça restaurativa e suas práticas no contexto escolar em um município de fronteira: limites e possibilidades - Souza, Carla Giselle Duenha de (2022)
Education is a fundamental right for all and has as one of its main goals the promotion of individual autonomy so that they can develop their abilities to relate to themselves, to others, and to the world. Furthermore, the school space is fundamental for the development of the human being, as it is a place capable of promoting social integration, the exchange of experiences, learning, and beyond, enabling the preparation for the future and for the exercise of citizenship. Thus, the school has an important social function in educating for survival, for freedom, for communication, and for transformation. In this sense, the social purpose of the school brings it closer to Restorative Justice, whose objective is to improve the climate, the safety and the learning at school, making use of universal human values such as: respect, honesty, humility, interconnection, responsibility, among others. Thus, through the implementation of restorative practices in education, especially Peacemaking Circles, the practice of authentic dialogue is proposed, guided by welcoming, by respect for the position of the other and by loving listening. This research aimed to study the Peacemaking Circles carried out in the Dr. Arnaldo Busatto border school in Foz do Iguaçu from a Freirian perspective. It was justified due to the relevance of the theme and the possible contribution to education. To this end, we used as theoretical reference Howard Zehr (2008, 2012, 2018, 2020), Kay Pranis (2010, 2011), Carolyn Boyles-Watson and Kay Pranis (2011, 2018), Katherine Evans and Dorothy Vaandering (2018), Elizabeth M. Elliot (2018) and Paulo Freire (2020, 2021). Having qualitative, descriptive and exploratory as the methodology used. Involving the realization of bibliographic research, documentary, field research and participant observation. By means of which, it can be verified that integral education is the one that sees the human being in its totality, that is, the one that observes, respects, and stimulates its social, cultural, physical, cognitive, and emotional dimensions, and that develops competencies in order to provide the formation of critical and reflective people. Thus, the use of dialogical practices on a regular basis in the school context is a collaborative and transformative tool for the promotion of a healthier school community and, consequently, for a better exercise of citizenship.